Effects of gasification biochar on plant-available water capacity and plant growth in two contrasting soil types - Hansen, Veronika; Hauggaard-Nielsen, Henrik; Petersen, Carsten T.; Mikkelsen, Teis Nørgaard; Müller-Stöver, Dorette (Soil & tillage research, 2016)
•Gasification biochar increased plant-available water capacity and soil pH.•Straw gasification biochar improved plant and root development in coarse sandy soil.•Wood gasification biochar had either no or slightly negative effect on plant growth. Gasification biochar (GB) contains recalcitrant carbon that can contribute to soil carbon sequestration and soil quality improvement. However, the impact of GB on plant-available water capacity (AWC) and plant growth in diverse soil types still needs to be explored. A pot experiment with spring barley (Hordeum vulgare L.) was conducted to investigate the effect of soil amendment by 1% straw and wood gasification biochar (SGB and WGB), respectively, on AWC and plant growth responses under two levels of water supply in a temperate sandy loam and a coarse sandy subsoil. In the sandy loam, the reduced water regime significantly affected plant growth and water consumption, whereas the effect was less pronounced in the coarse sand. Irrespective of the soil type, both GBs increased AWC by 17–42%, with the highest absolute effect in the coarse sand. The addition of SGB to coarse sand led to a substantial increase in plant biomass under both water regimes: shoot growth by 40–165% and root growth by 50–57%. However, no positive effects were achieved by the addition of WGB. In the sandy loam, soil application of GB had no or negative effects on plant growth. Our results suggest that SGB has considerable potential for enhancing crop productivity in coarse sandy soils by increasing soil water retention and improving root development.